The Anxiety in Speaking English by the Second Semester Students of English Department of FKIP UKI Toraja - Selvi Panggua (Teaching English as a Foreign Language Overseas Journal, 2019)
The objective of this research was to find out what factors cause the anxiety in speaking English by the Second Semester Students of English Department of FKIP UKI Toraja. In this research, the researcher used descriptive qualitative research with survey design. The researcher used interview as the way to get the data. The subject of this research was the Second Semester Students of English Department of FKIP UKI Toraja. The researcher used semi structure interview which consist of 10 questions. The data were analyzed by three steps, they are data reduction data display, and conclusion. The result of this research showed that mostly factors which caused the students anxiety in speaking English was difficult to adjust their accent with the British and American accents. And followed by less of self-confidence, and the other factors was listener understanding, pronunciation, and friends reaction. In this research, the researcher can concluded that British and American accent was the factor which mostly caused the students anxiety in speaking English by the second semester students of English Department of FKIP UKI Toraja.